Donor NKG2C Copy Number: An Independent Predictor for CMV Reactivation After Double Cord Blood Transplantation - Cao, Kai; Marin, David; Sekine, Takuye; Rondon, Gabriela; Zhao, Weicheng; Smith, Nathaniel T.; Daher, May; Wang, Qing; Li, Li; Saliba, Rima M.; Pingali, Ravi; Popat, Uday; et al. (Frontiers in Immunology, 2018)
Cytomegalovirus (CMV) remains a major cause of morbidity following allogeneic hematopoietic stem cell transplant. Natural killer cells expressing NKG2C have been shown to play a role in the immune surveillance of human CMV. We studied NKG2C copy number in the donor graft and the risk of CMV reactivation after double umbilical cord blood transplantation (DUCBT) in 100 CMV seropositive DUCBT recipients and their corresponding cord blood grafts (n=200). In the setting of DUCBT, the combined graft may contain 0 to 4 functional copies of NKG2C gene. Sixteen patients received a combined graft with 1 or 2 NKG2C copies and 84 patients were recipients of a combined graft with 3 or 4 NKG2C copies. The 6-month cumulative incidence of CMV reactivation for the two groups was 93.7% and 58.4% respectively (p=0.0003). In multivariate analysis, low NKG2C copies in the graft was an independent predictor of CMV reactivation (HR=2.72, CI=1.59-4.64; p<0.0001). Our study points to an important role for donor NKG2C for protection against CMV reactivation after DUCBT. These novel findings may help identify patients at a higher risk of CMV reactivation after DUCBT. Donor NKG2C genotype may be used as a potential criterion in the algorithm for graft selection for DUCBT.